Evaluation of Social and Economic Losses from Premature Mortality caused by HIV Infection - Podymova, Anzhelika Sergeevna; Baskakova, Irina Vladimirovna; Balandina, Marina Sergeevna (Economy of Regions, 2018)
The spread of HIV infection with the consequent death from AIDS removes some resources from the economy, impedes the preservation of human capital in the economy and undermines the foundations of economic development. The analysis of foreign and domestic research demonstrates the difficulty of assessing the impact of HIV infection on economic development. There is a variety of approaches and methods used for these assessments. Thus, the search for an optimal model to assess the impact of HIV infection on economic development becomes increasingly relevant. We have substantiated the calculation the economic burden of the disease caused by HIV infection. The proposed method for assessing socio-economic losses due to premature mortality from HIV infection includes three main types: the explicit economic costs from the premature mortality of the working-age population, the implicit costs from the premature mortality of the incapable population and the implicit economic costs from premature mortality of women of child-bearing age due to their inability to participate in the reproduction of the labour force. The magnitude of the region’s gross regional product (GRP) losses from fatal HIV infection increased 1.85 times between the years 2012 and 2016. As a result, of premature mortality from HIV infection, the Sverdlovsk oblast GRP decreased by 1.68 % in 2016, total losses were 16.2 billion roubles. In the structure of the total losses, about 70 % are implicit losses associated with the mortality of women of child-bearing age and therefore, the loss of the opportunity to increase the population of the region. The further direction of the research is to assess the socio-economic impact of investments in HIV treatment on the quality of life in the region.